Discussion questions about community-acquired pneumonia in children - N. A. Geppe; A. B. Malakhov; I. K. Volkov; I. A. Dronov (Сеченовский вестник)
This article discusses methods of diagnosis and treatment of community-acquired pneumonia in children, focuses on the practical issues of etiology and symptoms of the disease.